Upregulation of arylsulfatase B in carotid atherosclerosis is associated with symptoms of cerebral embolization - Erik Biros; Corey S. Moran; Jane Maguire; Elizabeth Holliday; Christopher Levi; Jonathan Golledge (Scientific Reports, 2017)
Abstract The aim of this study was to identify genes for which the expression within carotid atherosclerosis was reproducibly associated with the symptoms of cerebral embolization. Two publically available microarray datasets E-MEXP-2257 and GSE21545 were analysed using GeneSpring 11.5. The two datasets utilized a total of 22 and 126 carotid atherosclerosis samples, obtained from patients with and without symptoms of cerebral embolization, respectively. To assess whether the findings were reproducible we analysed carotid atherosclerosis samples from another 8 patients with and 7 patients without symptoms of cerebral embolization using real-time PCR. In vitro studies using VSMC were performed to assess the functional relevance of one of the validated genes. We identified 1624 and 135 differentially expressed genes within carotid atherosclerosis samples of symptomatic compared to asymptomatic patients using the E-MEXP-2257 and GSE21545 datasets, respectively (≥1.15-absolute fold-change, P < 0.05). Only 7 differentially expressed genes or 0.4% (7/1,752) were consistent between the datasets. We validated the differential expression of ARSB which was upregulated 1.15-fold (P = 0.029) in atherosclerosis from symptomatic patients. In vitro incubation of VSMCs with the ARSB inhibitor L-ascorbic acid resulted in marked upregulation of SIRT1 and AMPK. This study suggests that ARSB may represent a novel target to limit carotid embolization.